Low‐dose rapamycin prevents Ang‐II‐induced toxicity in Leydig cells and testicular dysfunction in hypertensive SHR model. Issue 9 (14th June 2022) - Kuo, Wei‐Wen; Baskaran, Rathinasamy; Lin, Jing‐Ying; Day, Cecilia Hsuan; Lin, Yueh‐Min; Ho, Tsung‐Jung; Chen, Ray‐Jade; Lin, Mei‐Yi; Padma, Viswanadha Vijaya; Huang, Chih‐Yang
Abstract: Hypertension is a common chronic cardiovascular disease reported among both men and women. Hypertension in males affects the testis and reproduction function; however, the pathogenesis is poorly understood. Rapamycin has been reported to have a variety of beneficial pharmacological effects; however, high‐doses rapamycin does have side effects such as immunosuppression. The present study investigates whether low‐dose rapamycin can reduce the damage caused by hypertension to the testis of spontaneously hypertensive rats (SHRs) and further examines molecular mechanism of low‐dose rapamycin in preventing testicular toxicity induced by angiotensin II (Ang II). Low rapamycin dose restores the testicle size, histological alterations, 3β‐hydroxysteroid dehydrogenase (3β‐HSD) expression, and prevents apoptosis in SHR rats. Ang II downregulates angiotensin‐converting enzyme‐2 (ACE2) expression through AT1R, p‐ERK, and MAS receptor in LC‐540 Leydig cells in a dose‐dependent manner. Low doses of rapamycin effectively upregulate steroidogenic enzymes, steroidogenic acute regulatory protein and 3β‐HSD expression in Leydig cells. Rapamycin upregulates ACE2 expression through p‐PKAc and p‐PI3k in Ang II‐treated cells. Further, rapamycin curbs mitochondrial superoxide generation and depleted mitochondrial membrane potential induced by Ang II through activation of Nrf2‐mediated Gpx4 and superoxide dismutase 2 expression. Our results revealed the involvement of ACE2, AT1R, AT2R, PKAc, and oxidative stress in Ang‐II‐induced testicular toxicity, suggesting low‐dose rapamycin could be a potential therapeutic candidate to attenuate testicular toxicity.